Las habilidades motoras para mejorar el dibujo infantil de las niñas y niños de 4 a 5 años de la escuela fiscal de educación básica Lauro Damerval Ayora de la ciudad de Loja. Periodo 2014-2015 - Mendoza Mejia, Nadia Lizethe (2016)
This research paper entitled: The motor to improve children's drawings of children of 4-5 years of the Fiscal School for Basic Education Lauro Damerval Ayora city of Loja skills. 2014-2015. It is structured and developed according to the Regulation Graduation force at the National University of Loja. It includes general objective: To develop motor skills to improve the child's drawing in children from 4-5 years. The methods used for the preparation of this research work were: scientific, deductive, inductive, descriptive, statistical, analytical and synthetic, also the techniques and instruments used were: the survey of teachers and Evaluation Handbook of Child Drawing applied the children of the Initial Level II which is aimed at girls (I) of the Fiscal School for Basic Education Lauro Damerval Ayora. It consisted of two teachers from the initial level II parallel (A and B) and 30 children who are 18 and 12 parallel A parallel B Fiscal School for Basic Education Lauro Damerval Ayora. It was concluded that: 100% of the teachers surveyed indicate that motor skills are important for improving children's drawings. In representing the child's drawing book: 57% of girls and boys are being observed to enhance a child's drawing. To reapply the observation guide after support activities 40% was an improvement in children's drawings. We conclude that the results of the survey concludes that 100% of the surveyed teachers report that motor skills play a decisive role in the development of children's drawings. Recommendation to the initial level II teachers, working in stimulating motor skills during daily work, motivating children through various exercises, recreational games and plastic works, so that children can develop properly and the teaching-learning process is satisfactory to them.